Technical And Human Challenges Facing Saudi Red Crescent Teams In Dealing With Traffic Accidents (The Review of Diabetic Studies, 2025)
This study examines the technical and human challenges facing Saudi Red Crescent teams in dealing with traffic accidents, as they are among the most demanding field situations, requiring rapid response and high efficiency. The importance of the study stems from the vital role these teams play in saving lives and mitigating the effects of injuries, given the increasing reliance on modern technology in emergency and first aid care. The study relied on the descriptive analytical approach as it is the most appropriate for monitoring and analyzing field phenomena. A questionnaire was designed consisting of a set of items that measure the technical and human aspects of the challenges. The questionnaire was distributed to a sample of (200) individuals from the Saudi Red Crescent teams working in the field, with the aim of collecting comprehensive and reliable data that reflects the practical reality. The results revealed that the technical challenges were represented by the difficulty of dealing with digital systems and smart applications, the weakness of the technical infrastructure in some locations, and the ongoing need for training on modern devices. Human challenges included the psychological and physical stresses team members face during incident response, some employees' resistance to change when new technologies are introduced, and lack of experience using electronic systems. The study concluded that these challenges directly impact the efficiency of emergency response and the speed of field intervention. This highlights the need to develop sustainable training plans, provide ongoing technical support, and enhance human readiness through advanced training programs, in addition to investing in digital infrastructure to ensure improved quality of services provided in traffic accident cases.